THE EFFECT OF PRODUCT QUALITY, SERVICE QUALITY, BRAND IMAGE AND PRICE SUITABILITY ON CUSTOMER SATISFACTION: (CASE STUDY ON CONSUMERS OF SCRARLETT WHITENING PRODUCTS) - Taiso, Theresia Irene; Udayana, Ida Bagus Nyoman; Maharani, Bernadetta Diansepti (Universitas Ibn Khaldun Bogor, 2024)
This research is categorized into hypothesis testing. The type of this research is quantitative. This research aims to analyze the influence of product quality on customer satisfaction, service quality influences customer satisfaction, brand image influences customer satisfaction, and price appropriateness influences customer satisfaction with Scarlett Whitening products. The samples taken were 100 respondents who were consumers of Scarlett Whitening products who bought the product twice. This research uses the Purposive Sampling method with the technique used in this research using a questionnaire. Based on the results of this research, it was found that product quality does not have a positive and significant effect on customer satisfaction, this is proven by the t-count value of -0.432 and a significant value of 0.66 > 0.05. Service quality has a positive and significant effect on customer satisfaction as evidenced by the t-count value of 4.223 and a significant value of 0.00 <0.05. Brand image has a positive and significant effect on customer satisfaction as evidenced by the t-value of 5.669 and a significant value of 0.00 <0.05. Price feasibility does not have a positive and significant effect on customer satisfaction as evidenced by the t-value of -0.361 and a significant value of 0.71>0.05.